Adverse childhood experiences do not moderate the association between aggressive antisocial behavior and general disinhibition in a forensic psychiatric inpatient sample - Meddeb, Adam; Berlin, Johan; Laporte, Natalie; Wallinius, Märta (Frontiers in Psychology, 2022)
Adverse childhood experiences (ACE) and high levels of disinhibition have been associated with a variety of negative outcomes such as aggressive antisocial behavior (AAB). However, forensic psychiatric populations remain an understudied group in this field of research. This study aimed to fill that gap by investigating associations between ACE, AAB, and disinhibition in a forensic psychiatric sample. Furthermore, we aimed to explore such findings by investigating whether ACE might have a moderating effect on the association between disinhibition and AAB. A sample of forensic psychiatric patients (n = 89) was recruited from a high-security forensic psychiatric facility in Sweden. All study variables were moderately to strongly related to each other, although we found no moderating effect of ACE. Post hoc analysis indicated that our ACE items had differential effects on AAB scores, with placement outside the family home, absent parents, and parental drug abuse producing the largest effect on AAB levels. Our findings are in line with previous research demonstrating a significant and robust relationship between ACE, AAB, and disinhibition. Forensic psychiatric populations are exposed to high levels of both self-reported and documented ACE. This calls for trauma-informed care and highlights the importance of considering ACE in risk assessment, preventive work, and policy making.